2012
DOI: 10.1152/jn.01144.2011
|View full text |Cite
|
Sign up to set email alerts
|

Handedness but not dominance influences variability in endurance time for sustained, submaximal contractions

Abstract: Gordon NM, Rudroff T, Enoka JA, Enoka RM. Handedness but not dominance influences variability in endurance time for sustained, submaximal contractions. J Neurophysiol 108: 1501-1510. First published June 13, 2012 doi:10.1152/jn.01144.2011The purpose of this study was to compare endurance time and accompanying neuromuscular adjustments when left-and right-handed subjects used the dominant and nondominant arms to sustain submaximal contractions that required either force or position control. Ten left-handed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…However, no significant difference between hands was found for persons with MS, possibly linked to disease-related muscle weakness (8). Similarly, fatigability was not different between dominant and non-dominant hand, either in healthy controls or in persons with MS. these results are consistent with those of Gordon et al, who reported an equal fatigability of the upper limb in a sample of healthy persons during a submaximal contraction for the dominant and non-dominant arms (20). there were moderate correlations between fatigue indices of the dominant and non-dominant hands and between the more and less affected hands, possibly indicating on a central origin of muscle fatigue, as suggested in previous research (17).…”
Section: Hand Grip Fatigability According To Disease Stagesupporting
confidence: 93%
See 1 more Smart Citation
“…However, no significant difference between hands was found for persons with MS, possibly linked to disease-related muscle weakness (8). Similarly, fatigability was not different between dominant and non-dominant hand, either in healthy controls or in persons with MS. these results are consistent with those of Gordon et al, who reported an equal fatigability of the upper limb in a sample of healthy persons during a submaximal contraction for the dominant and non-dominant arms (20). there were moderate correlations between fatigue indices of the dominant and non-dominant hands and between the more and less affected hands, possibly indicating on a central origin of muscle fatigue, as suggested in previous research (17).…”
Section: Hand Grip Fatigability According To Disease Stagesupporting
confidence: 93%
“…one may hypothesize a higher fatigability in the non-dominant compared with the dominant hand in persons with MS with higher EdSS scores, since these persons with MS use their dominant arm more in daily life (8). However, if pathological muscle fatigue in persons with MS is mainly of central origin, one could also hypothesize that there would be no difference between dominant and non-dominant hands, nor between the more and less affected sides, which could be supported by reports in healthy persons, stating that fatigability did not seem to differ between dominant and non-dominant hands (20). to our knowledge, the difference in fatigability between dominant and non-dominant hands has not been assessed in persons with MS.…”
mentioning
confidence: 86%
“…The groups were not matched on handedness. This is not likely to cause problems with interpretation of the results, as it was already reported that fatigability does not differ between right-handed and left-handed persons [ 43 ] and only 3 out of 16 PwMS were left-handed. Further, although we aimed to test the dominant arm in all subjects, two PwMS performed the tests with their non-dominant hand.…”
Section: Discussionmentioning
confidence: 73%
“…As handedness has been shown to have a significant impact in upper-extremity muscle activity, [14][15][16][17][18][19] the VRIs were All subjects were male (29 ± 4 years of age, 22-36 years of age). Mean height was 177.9 ± 9.3 cm and mean weight was 80.9 ± 8.1 kg.…”
Section: Subjects and Assessment Protocolmentioning
confidence: 99%